Adesão à terapia farmacológica por adultos usuários do componente especializado da assistência farmacêutica e fatores associados, São Leopoldo-RS - Fritzen, Janaina Soder (Universidade do Vale do Rio dos Sinos, 2015)
The promotion of the rational use of medicines depends not only on their availability but also on the subject's adherence to the treatment. Studies have shown that the prevalence of essential medicines adherence vary from 15-17%, while the adherence to the Specialized Component of Pharmaceutical Care (CEAF) ones is still unknown. It was aimed to evaluate the adherence prevalence of CEAF medicines and related facts, among which the regular access to the treatment. This is a transversal study on CEAF medicine adult users aged 20 and more in the city of Sao Leopoldo, RS. A consecutive sampling of users who had access to CEAF service from December 2014 to March 2015 was carried out. By the aid of a standardized questionnaire, the sampling was characterized according to social-demographic, behavioral, nutritional, health, and medicine usage habit variables. The adherence to the medicines in the last week was measured by Brief Medication Questionnaire (BMQ) on diet, belief and recollection realms. It was labeled as adherent the users that didn't show barriers to the adherence of the three realms. The regular access to the medicine was defined as the free or paid acquisition of all medications in the last three months. Poisson Regression was used with robust variation. 414 users, mostly women (60.9%), only CEAF medicine users (68.1%), average age 55 (DP=13) were interviewed in an average of 7.3 years of study. The prevalence of adherence was 28.3%, being free regular access 46.1%. After adjusting to the number of medicines CEAF and number of medicines of continuous use, users who had free regular access showed 60% more probability of adherence than those without regularity. Regarding the individuals with regular paid access, the link between access and adherence wasn't verified. The data have shown low prevalence of adherence and the impact of the regularity of the user's free access. The programme for getting the CEAF medicines is indispensable for avoiding the irregular access to these medicines, which shows an important restriction in the medicines policies.
Keywords: Uso de medicamentos; Adesão à medicação; Acesso aos serviços de saúde; Assistência farmacêutica; Farmacoepidemiologia; Drug utilization; Medication adherence; Health services accessibility; Pharmaceutical assistance; Pharmacoepidemiology; ACCNPQ::Ciências da Saúde::Saúde Coletiva